Clinical performance of subcutaneous vs. transvenous implantable defibrillator in patients with ischemic cardiomyopathy: data from Monaldi Rhythm Registry - Russo, Vincenzo; Caturano, Alfredo; Bianchi, Valter; Rago, Anna; Ammendola, Ernesto; Papa, Andrea Antonio; Della Cioppa, Nadia; Guarino, Annamaria; Masi, Alessandro; D'Onofrio, Antonio; Golino, Paolo; Di Lorenzo, Emilio; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSubcutaneous ICD (S-ICD) is an alternative to a transvenous implantable cardioverter-defibrillator (TV-ICD) system in selected patients not in need of pacing or resynchronization. Currently, little is known about the effectiveness and safety of S-ICD in patients with ischemic cardiomyopathy (ICM). The aim of our study was to describe the clinical features and the drivers of S-ICD implantation among patients with ICM, as well as the clinical performance of S-ICD vs. TV-ICD among this subset of patients during a long-term follow-up.Materials and methodsAll ICM patients with both S-ICD and TV-ICD implanted and followed at Monaldi Hospital from January 1, 2015, to January 1, 2024, were evaluated; among them, only ICD recipients with no pacing indication were included. We collected clinical and anamnestic characteristics, as well as ICD inappropriate therapies, ICD-related complications and infections.ResultsA total of 243 ICM patients (mean age 63.0 ± 11.0, male 86.0%) implanted with TV-ICD (n: 129, 53.1%) and S-ICD (n: 114, 46.9%) followed at our center for a median follow-up of 66.9 [39.4–96.4] months were included in the study. Kaplan–Meier analysis revealed no significant difference in the risk of inappropriate ICD therapies (log-rank p = 0.137) or ICD-related complications (log-rank p = 0.055) between S-ICD and TV-ICD groups. TV-ICD patients showed a significantly higher risk of ICD-related infections compared to those in the S-ICD group (log-rank p = 0.048). At multivariate logistic regression analysis, the only independent predictors of S-ICD implantation were female sex [OR: 52.62; p < 0.001] and primary prevention [OR: 17.60; p < 0.001].ConclusionsAmong patients with ICM not in need of pacing or resynchronization (CRT), the decision to implant an S-ICD was primarily influenced by female gender and primary prevention indications. No significant differences in inappropriate ICD therapies and complications were found; in contrast, the S-ICD group showed a numerically reduced risk of ICD-related infections.